Antibiotic residues in poultry food in Fujian Province of China. Issue 3 (2nd July 2020) - Yang, Yan; Qiu, Wenqian; Li, Yuxiang; Liu, Lijing
ABSTRACT: Thirty-nine kinds of antibiotics (11 quinolones, 10 tetracyclines, and 18 sulphonamides) residues were screened in 146 samples including chicken, chicken giblets, and eggs in Fujian by ultra-performance liquid chromatography–tandem mass spectrometry (LC-MS/MS) and analysed the contamination status of antibiotic residues.seventeen kinds of antibiotics were detected, with an overall detection rate of 47.3% and the exceeding rate was 11.6%. Antibiotics were found in 46.7% chicken, 72.2% chicken giblets, and 30% eggs. In 11.1% of chicken giblets and 26% of eggs, the detected concentration exceeded the maximum residue level (MRLs). The total detection rate of tetracycline antibiotics was higher than that of quinolones (33.6% vs. 24.7%) and the sulphonamides (33.6% vs. 4.8%). The exceeding rates of tetracyclines, quinolones, and sulphonamides were 2.7%, 10.3%, and 1.4%, respectively. We suggested that the abuse of antibiotics in poultry foods still exists, and more attention should be paid to the antibiotic residues in poultry eggs.